PROFESSION – SPECIFIC LANGUAGE TOOLS THAT IMPLEMENT THE VOCATIONAL LEXICON CATEGORY - Imomov Elyor Abdikarimovich (Galaxy International Interdisciplinary Research Journal, 2022)
Lexicology studies words and their meaning. So it is essential part of linguistics. The purpose of the article is to research specific tools for professional words that implement the vocational lexicon category. Moreover, it shows the origin of some words.